Recovery of a single link failure in all-optical networks based on the cuckoo search algorithm. (6th January 2022) - Kumar, Dinesh; Kumar, Rajiv; Sharma, Neeru
This paper presents a problem of a link failure in all types of optical networks. Here, the concept of monitoring path (MPs) and monitoring cycles (MCs) has been introduced for the identification of single-link failures in optical networks. MPs and MCs need to go through one or more monitoring locations. These monitoring locations are established such that any single failure in the optical networks is the combination of MPs and MCs, which pass through the different monitoring locations. For a single monitoring location in the network, the three-edge connectivity is a essential condition for establishing the MPs and MCs to distinctively identify the single link failure in the network. We evaluate the performance of network parameters like bandwidth blocking probability (BBP), recovery time and bandwidth provisioning ratio (BPR) for dedicated path protection (DPP), shared path protection (SPP), and proposed survivable scheme (PSS). The proposed system is validated in MATLAB software.